2020
DOI: 10.1038/s41598-020-64674-1
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α agonist-induced suppression of 3T3-L1 cell adipogenesis affects spatial formation of extra-cellular matrix

Abstract: To establish a deepening of the upper eyelid sulcus (DUES) model that can be induced by prostaglandin (PG) analogues, a three-dimension (3D) tissue culture was employed. Upon adipogenesis of the 3T3-L1 organoid, the effects of either Bimatoprost acid (BIM-A), or PGF2α were examined. During the adipogenesis, organoid size, lipid staining by BODIPY and expression of the extracellular matrix (ECM) by immunocytochemistry and/or quantitative PCR were employed. The size of the organoid increased remarkably during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
156
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(179 citation statements)
references
References 40 publications
(46 reference statements)
23
156
0
Order By: Relevance
“…Furthermore, these changes in ECM expression also were different between the 2D and 3D culture experiments. This observation was not surprising because in our precedent study using trypsin digestion 16 , the breakdown times of 3D organoids from preadipocytes of 3T3-L1 cells were much longer than the corresponding values for a similar 2D cell culture, and the values for 3D organoids were further enhanced upon adipogenesis. Furthermore, we also performing quite unique analyses, i.e.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Furthermore, these changes in ECM expression also were different between the 2D and 3D culture experiments. This observation was not surprising because in our precedent study using trypsin digestion 16 , the breakdown times of 3D organoids from preadipocytes of 3T3-L1 cells were much longer than the corresponding values for a similar 2D cell culture, and the values for 3D organoids were further enhanced upon adipogenesis. Furthermore, we also performing quite unique analyses, i.e.…”
Section: Discussionmentioning
confidence: 75%
“…To study this issue further, 3D organoid cultures of 3T3-L1 cells which are known to be a more representative disease model for DUES 16 , were used. Consistent with our preceding study, the sizes of the uniform round-shape spheroidal organoids of 3T3-L1 cells were smaller than the matured forms during the 7-day culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this technique, we were able to obtain 3D organoids from HOF in patients with TAO using a drop culture method, and found that HIF2A played a critical role in mediating LOX-dependent ECM accumulation 25 . More recently, to elucidate the molecular etiology of DUES induced by PGs, we employed this 3D culture system using HOF and 3T3-L1 cells, and found that PGs significantly suppressed 3D organoid sizes, and modulated the spatial distribution of several ECMs surrounding the 3D organoids 26 , 27 . We therefore concluded that our developed 3D cell culture would be suitable for investigating the molecular etiology of TAO and DUES and also will be applicable for use in many other cells and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these studies involved the use of conventional 2D cell cultures, despite the fact that the HTM is composed of multiple sheets in the human eye 24 , thus a relevant 3D cell culture model should be used in this research field. Our group recently established a 3D cell culture system using 3T3-L1 cells or human orbital fibroblasts (HOF) as disease models for thyroid associated orbitopathy (TAO) 25 , and the deepening of the upper eyelid sulcus (DUES) induced by prostaglandin analogues (PGs) 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%